2020
DOI: 10.1111/jam.14578
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of livestock‐associated methicillin‐resistantStaphylococcus aureusclonal complex 398 andmecCMRSA among human isolates in North‐West England

Abstract: Aims Livestock‐associated methicillin‐resistant Staphylococcus aureus (LA‐MRSA) is an important public health problem in many countries. Despite reports of such isolates being found in both animals and humans in the United Kingdom few data are available on the prevalence in humans of such isolates. A prevalence study was therefore undertaken in the north‐west of England. Methods and Results One thousand two hundred and forty‐two human MRSA isolates collected during 2015 were screened by PCR to detect two of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Several studies did not identify any mecC -positive S. aureus among included human isolates/samples ( Table 2 ) [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. In studies in which this gene was detected ( Table 1 ), the prevalence identified, considering the total number of isolates/samples included, was < 1% in most of the cases [ 24 , 27 , 28 , 29 , 32 , 33 , 37 , 40 , 41 , 42 , 43 ], similar to that identified in the first study in which mecC was discovered (approximately 0.04%) [ 16 ]. In a few studies, the prevalence was > 1% but, in all of these, only a small number of initial isolates (<400 isolates) was used; this ma...…”
Section: Detection Of Mecc -Mrsa Isolates In Husupporting
confidence: 71%
See 4 more Smart Citations
“…Several studies did not identify any mecC -positive S. aureus among included human isolates/samples ( Table 2 ) [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. In studies in which this gene was detected ( Table 1 ), the prevalence identified, considering the total number of isolates/samples included, was < 1% in most of the cases [ 24 , 27 , 28 , 29 , 32 , 33 , 37 , 40 , 41 , 42 , 43 ], similar to that identified in the first study in which mecC was discovered (approximately 0.04%) [ 16 ]. In a few studies, the prevalence was > 1% but, in all of these, only a small number of initial isolates (<400 isolates) was used; this ma...…”
Section: Detection Of Mecc -Mrsa Isolates In Husupporting
confidence: 71%
“…Since then, several retrospective and prospective studies using human S. aureus isolates/samples were carried out in order to search for mecC -MRSA isolates ( Table 1 and Table 2 ) [ 16 , 18 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ,…”
Section: Detection Of Mecc -Mrsa Isolates In Humentioning
confidence: 99%
See 3 more Smart Citations